Parental Background and Intergenerational Occupational Mobility - Germany and the United States compared - Eberharter, Veronika (Journal of Income Distribution®, 2008)
Using longitudinal data from the GSOEP-PSID Equivalent File 1980-2002 we analyze the extent and structure of intergenerational occupational mobility and the determinants of occupational choice in Germany and the United States two countries with different social role patterns. We find empirical evidence of a higher exchange (or circulation) mobility in the United States, which corroborates its being a more open society than Germany. The results of the multinomial logit model of occupational choice supports human capital theory hypotheses: occupational choice is gender specific, and more educated persons are more likely to perform occupational success. The influence of family background variables on occupational choice, too, partly supports the impact in Germany of traditional role patterns and in American society of the higher social permeability.